Estimation of heterosis in diverse cytoplasmic male sterile sources of Pearl millet [Pennisetum glaucum (L.) R. Br.] - Amiribehzadi, Alidad; Satyavathi, C. Tara; Singh, S.P.; Bharadwaj, C.; Singh, Madan Pal (Annals of Agricultural Research, 2014)
Among the available sources of cytoplasmic male sterility only the A1 source has so far been exploited for developing commercial hybrids in pearl millet (Pennisetum glaucum (L.) R. Br.). In the present study, heterosis over better parent and commercial check were estimated in lines belonging to A1, A4 and A5 cytoplasms for fifteen yield attributing and physiological traits. Heterosis was observed in A1 source for plant height, days to maturity, spike girth, 1000 seed weight, harvest index, chlorophyll a, carotenoid content and membrane stability index. For days to 50% flowering, number of productive tillers per plant, spike length, grain yield per plant, biomass and chlorophyll b, heterosis was observed in lines belonging to A4 cytoplasmic source. Significant heterotic values were observed for panicle harvest index in A5 cytoplasm.